Evaluation of Google and Bing online translation of verb-noun collocations from English into Arabic - Soori, Hussein; Awab, Su’ad (Journal of Modern Languages, 2015)
This article aims to investigate and evaluate the translation of verb-noun collocation in English into Arabic Google and Bing online translation engines. A number of sentences were used as a testing dataset to evaluate both engines. Human translations by three bilingual speakers were used as a gold standard. A simple evaluation metric was proposed to calculate the translation accuracy of verb-noun collocations. The results showed that Bing scored a verb-noun collocation value of 0.72 with a trend estimation ranging between 0.65 and 0.67. Google scored a verb-noun collocation value of 0.75 (3% higher than Bing) with a trend estimation ranging between 0.63 and 0.85. The results also showed that, in most cases, the Arabic translation output of both engines produced a one verb synonym which did not collocate with the different nouns in the testing data sentences. These results indicate that Google and Bing, so far, have not been able to resolve the verb-noun collocability problem in their Arabic output. This study and its results may shed some light on the problem and to develop new methods to improve Arabic verb noun collocability in the output translation of current machine translation engines.